Antimicrobial Susceptibility and Apparent Multidrug Resistance Screening Patterns of Bacterial Pathogens Recovered from Clinical Samples of Companion Animals in Jordan, 2012–2024: A Retrospective Study from a Veterinary Teaching Hospital - Mays Malkawi; Mousa Daradka; Zuhair Bani Ismail (Veterinary Sciences, 2026)
Antimicrobial resistance is an increasing concern in veterinary medicine and within the One Health framework, yet long-term data from companion animals remain limited in Jordan. This retrospective study characterized bacterial pathogens and archived antimicrobial susceptibility patterns among clinical samples from dogs and cats presented to the Veterinary Teaching Hospital of Jordan University of Science and Technology between 2012 and 2024. Records from 232 clinical cases comprising 248 submitted samples were reviewed. Among 237 samples with known culture outcomes, 121 yielded bacterial growth (51.1%), resulting in 141 bacterial isolates. Escherichia coli (E. coli) (33.3%) was the most frequently recovered organism, followed by Staphylococcus aureus (S. aureus) (19.1%), Staphylococcus spp. (15.6%), and Proteus spp. (9.9%). AST results were available for 96/141 isolates (68.1%). Archived interpretations showed frequent non-susceptibility to several tested agents, whereas fluoroquinolone non-susceptibility was generally lower. Using the historical study rule of non-susceptibility to at least one agent in three or more antimicrobial classes, 87/96 isolates (90.6%) met the screening criterion. However, intermediate results were grouped with resistant results, AST panels and breakpoint standards varied over 13 years, and the archived records did not permit reliable exclusion of intrinsic resistance for every organism–drug combination. Accordingly, the MDR estimate is descriptive and should not be interpreted as a standardized contemporary prevalence. These data provide a baseline for companion-animal bacterial surveillance in Jordan and support prospective standardized AST and antimicrobial stewardship.